Expected Genetic Gains from Forest Tree Breeding - Venkatesh, C. S. (Indian Forester, 1976)
The kind and magnitude of practical gains realisable through the application of genetics in forestry, are outlined. It is concluded that by adopting different Relection procedures and breeding methods, substantial economic gains can accrue to the forest grower as well as the forest based industry. The plea is therefore made that the state forest departments and the industries in this country adopt these without any further delay, and reap the economic benefits that can be realised thereby.